Transcriptome Landscape of Human Folliculogenesis Reveals Oocyte and Granulosa Cell Interactions - Zhang, Yaoyao; Yan, Zhiqiang; Qin, Qingyuan; Nisenblat, Vicki; Chang, Hsun-Ming; Yu, Yang; Wang, Tianren; Lu, Cuiling; Yang, Ming; Yang, Shuo; Yao, Ying; Zhu, Xiaohui; et al. (Molecular cell, 2018)
The dynamic transcriptional regulation and interactions of human germlines and surrounding somatic cells during folliculogenesis remain unknown. Using RNA sequencing (RNA-seq) analysis of human oocytes and corresponding granulosa cells (GCs) spanning five follicular stages, we revealed unique features in transcriptional machinery, transcription factor networks, and reciprocal interactions in human oocytes and GCs that displayed developmental-stage-specific expression patterns. Notably, we identified specific gene signatures of two cell types in particular developmental stage that may reflect developmental competency and ovarian reserve. Additionally, we uncovered key pathways that may concert germline-somatic interactions and drive the transition of primordial-to-primary follicle, which represents follicle activation. Thus, our work provides key insights into the crucial features of the transcriptional regulation in the stepwise folliculogenesis and offers important clues for improving follicle recruitment in vivo and restoring fully competent oocytes in vitro. [Display omitted] •RNA-seq of oocytes and granulosa cells mapped transcriptome and signature genes•KEGG/GSEA analysis uncovered pathways involved in primordial follicle activation•Oocyte-granulosa cell interactions exhibit stage- and species-specific patterns•RNA-seq analysis identified candidate secretory biomarkers of ovarian reserve Zhang et al. investigated the transcriptomic profiles from both the oocyte and somatic follicular compartments during folliculogenesis using single-cell RNA-seq analysis. They provided a transcriptomic landscape of folliculogenesis as well as key insights into the transcriptional regulation in oocytes and granulosa cells during the stepwise folliculogenesis.